2019
DOI: 10.1021/acsnano.8b09283
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Limits to the Coupling between Light and 2D Polaritons by Small Scatterers

Abstract: Polaritonic modes in two-dimensional van der Waals materials display short in-plane wavelengths compared with light in free space. As interesting as this may look from both fundamental and applied viewpoints, such large confinement is accompanied by poor in/out optical coupling, which severely limits the application of polaritons in practical devices. Here, we quantify the coupling strength between light and 2D polaritons in both homogeneous and anisotropic films using accurate rigorous analytical methods. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…In Fig. 2, we show the dispersion relations of three types of plasmonic modes supported by the structures sketched in the insets at three different graphene electron temperatures T e , as calculated using methods discussed in previous studies 37,41,54 . In all cases considered in Fig.…”
Section: Thermoplasmonic Properties Of Atomically Thin Filmsmentioning
confidence: 96%
“…In Fig. 2, we show the dispersion relations of three types of plasmonic modes supported by the structures sketched in the insets at three different graphene electron temperatures T e , as calculated using methods discussed in previous studies 37,41,54 . In all cases considered in Fig.…”
Section: Thermoplasmonic Properties Of Atomically Thin Filmsmentioning
confidence: 96%
“…These two properties make vdW materials an effective and compact platform for active modulation of both guided waves and free space light at mid‐infrared frequencies. The extremely confined nature of vdW plasmons, however, makes them difficult to couple strongly to the free waves and thus hinders their efficiency in optoelectronic devices . Recent advances have shown that this wavevector mismatch problem can be overcome by introducing multiscale nanophotonic design, which enables electronically tunable perfect absorption in graphene …”
Section: Dynamic Light Modulation With Tunable Plasmonsmentioning
confidence: 99%
“…Despite these efforts, strong light modulation using graphene nanoresonators has been elusive due to the inefficient coupling between the graphene plasmons and free space photons. This weak coupling is, in fact, related to the large confinement factors of graphene plasmons, which is—in principle—a desirable property, but also creates a large mismatch between the free space and graphene plasmon optical wavelengths . In other words, scattering cross sections in graphene nanoresonators are limited by the inherent large momentum mismatch.…”
Section: Dynamic Light Modulation With Tunable Plasmonsmentioning
confidence: 99%
See 2 more Smart Citations